Geomorphological techniques - Goudie, Andrew (Routledge, 1994)
This book includes a new chapter on neotectonics, and updated sections on remote sensing, image analysis, radiometric dating, geomorphometry, data loggers, radioactive tracers, and the determination of pore water pressure and of the rates of denudation. New illustrations have been added and the recent profusion of literature is reflected in an extensive bibliography of mor than a thousand references